2022
DOI: 10.1039/d2sc01264b
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art accounts of hyperpolarized 15N-labeled molecular imaging probes for magnetic resonance spectroscopy and imaging

Abstract: Hyperpolarized isotope-labeled agents have significantly advanced nuclear magnetic resonance spectroscopy and imaging (MRS/MRI) of physiochemical activities at molecular levels. An emerging advance in this area is exciting developments of 15N-labeled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…15 N generally offers longer T 1 relaxation times than 13 C due to its lower gyromagnetic ratio. 15 N labeled heteroaromatic molecules such as nicotinamide and metronidazole can be efficiently hyperpolarized using parahydrogen based methods (SABRE). These compounds are also known to bind to albumin with a K a of around 10 5 M –1 and consequently, albumin binding is expected to shorten the 15 N T 1 values. , …”
mentioning
confidence: 99%
“…15 N generally offers longer T 1 relaxation times than 13 C due to its lower gyromagnetic ratio. 15 N labeled heteroaromatic molecules such as nicotinamide and metronidazole can be efficiently hyperpolarized using parahydrogen based methods (SABRE). These compounds are also known to bind to albumin with a K a of around 10 5 M –1 and consequently, albumin binding is expected to shorten the 15 N T 1 values. , …”
mentioning
confidence: 99%
“…The facile synthesis of 15 N-labeled anilines further demonstrates the utility of this method. 15 N-labeled compounds are of significance in studying the pharmacokinetics and metabolism of bioactive compounds are usually prepared by a nitration–reduction process with 15 N-labeled nitric acid as the nitrogen source. , As summarized in Table , using this light-driven Ni­(II)-catalyzed C–N coupling reaction, 15 N-labeled anilines could be readily accessed with commercially available 15 NH 4 Cl, a cheaper and more conveniently handled nitrogen-15 source.…”
Section: Resultsmentioning
confidence: 99%
“…With currently limited reports on in vivo studies of 15 N-probes, 15 N-BBCP presents exciting progress as an exogenous reaction-based 15 N-probe extended to in vivo imaging. While 15 N-BBCP was rationally designed to achieve the desired molecular reactivity, several factors need to be considered and improved for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to carbon-13-labeled probes, nitrogen-15-labeled agents are relatively underexplored as hyperpolarization probes. Among the hyperpolarization studies reported, the 15 N-labeled hyperpolarized probes have shown great potentials to deliver a long T 1 and a wide range of 15 N chemical shift (900 ppm) for an extended scope of chemical complexity. Notably, the T 1 of 15 N-trimethylphenylammonium was reportedly over 400 s although the oxidative reaction afforded a small chemical shift (∼1.5 ppm).…”
mentioning
confidence: 99%